Genome‐wide expression analysis and EMX2 gene expression in embryonic myoblasts committed to diverse skeletal muscle fiber type fates. Issue 8 (24th June 2013) - Weimer, Kristina; Theobald, Jillian; Campbell, Kenneth S.; Esser, Karyn A.; DiMario, Joseph X.
<x xml:space="preserve">Abstract</x> Background: Primary skeletal muscle fibers form during embryonic development and are characterized as fast or slow fibers based on contractile protein gene expression. Different avian primary muscle fiber types arise from myoblast lineages committed to formation of diverse fiber types. To understand the basis of embryonic muscle fiber type diversity and the distinct myoblast lineages that generate this diversity, gene expression analyses were conducted on differentiated muscle fiber types and their respective myoblast precursor lineages. Results: Embryonic fast muscle fibers preferentially expressed 718 genes, and embryonic fast/slow muscle fibers differentially expressed 799 genes. Fast and fast/slow myoblast lineages displayed appreciable diversity in their gene expression profiles, indicating diversity of precursor myoblasts. Several genes, including the transcriptional regulator EMX2, were differentially expressed in both fast/slow myoblasts and muscle fibers vs. fast myoblasts and muscle fibers. EMX2 was localized to nuclei of fast/slow myoblasts and muscle fibers and was not detected in fast lineage cells. Furthermore, EMX2 overexpression and knockdown studies indicated that EMX2 is a positive transcriptional regulator of the slow myosin heavy chain 2 (MyHC2) gene promoter activity in fast/slow muscle fibers. Conclusions: These results indicate the presence of distinct molecular signatures that characterize diverse embryonic myoblast lineages before differentiation. Developmental Dynamics 242:1001–1020, 2013. © 2013 Wiley Periodicals, Inc.